Theophylline-loaded pectin-based hydrogels. II. Effect of concentration of initial pectin solution, crosslinker type and cation concentration of external solution on drug release profile - BATIREL, SAİME (WILEY, 2019)
A series of drug-loaded pectin hydrogels were prepared by mixing method in two ion types, Ca+2 or Zn+2, for wound dressing applications and their drug release performances were investigated at pH 6.4 in four different calcium ion concentrations of external solution. Pectin hydrogels were synthesized in three different concentrations of initial pectin solution and theophylline was used as a model drug. Fourier transform infrared spectroscopy, scanning electron microscopy, and atomic force microscopy were used for hydrogel characterization. Additionally, fluid handling capacity, swelling behavior, dehydration rate, dispersion characteristic, dressing pH determination, water vapor permeability, oxygen permeability, surface contact angle, flexibility, mass per unit area, and thickness were determined for selected hydrogels. One of the most valuable contributions of our study is that the concentration of initial pectin solution and calcium ion concentration of external solution are very important parameters to obtain an effective drug release. After evaluating all data, we have shown that flexible and transparent pectin-based wound dressings can be synthesized as a controlled drug release system. Zinc-containing hydrogel was antibacterial against Staphylococcus aureus and Escherichia coli but not suitable for cell migration. On the other hand, calcium-based hydrogel was nontoxic on the fibroblast cells and it had no negative effect on cell migration. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48155.
Keywords: antibacterial activity; cytotoxicity activity; hydrogel; pectin; theophylline; ZINC-OXIDE NANOPARTICLES; BIOMEDICAL APPLICATIONS; WOUND DRESSINGS; CITRUS PECTIN; CALCIUM; ANTIBACTERIAL; ALGINATE; BINDING; THIOCYANATE; MONOVALENT